2012
DOI: 10.3390/v4123701
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus in Systemic Lupus Erythematosus, Rheumatoid Arthritis and Multiple Sclerosis—Association and Causation

Abstract: Epidemiological data suggest that the Epstein-Barr virus (EBV) is associated with several autoimmune diseases, such as systemic lupus erythematosus, rheumatoid arthritis and multiple sclerosis. However, it is not clear whether EBV plays a role in the pathogenesis of these diseases, and if so, by which mechanisms the virus may contribute. In this review, we discuss possible viral and immunological mechanisms that might explain associations between EBV and autoimmune diseases and whether these associations repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 219 publications
(272 reference statements)
1
93
0
7
Order By: Relevance
“…(Jones and Straus 1987;Miller et al 1987). In general, individuals with aberrant (elevated) levels of EA(D) antibodies, are considered to (temporally) lack proper immunological control over endogenous latent EBV, resulting in increased viral reactivation and replication and re-expression of immunogenic early antigens, as observed in "stress" and "fatigue" cohort studies (Glaser et al 2005;Lerner et al 2012), but which are also observed in patients with certain autoimmune disorders, such as SLE and RA (Ballandraud et al 2004;Lossius et al 2012), and nasopharyngeal carcinoma (Paramita et al 2007). …”
Section: Ebv Humoral Immune Responses As Defined By Classic Serology mentioning
confidence: 99%
“…(Jones and Straus 1987;Miller et al 1987). In general, individuals with aberrant (elevated) levels of EA(D) antibodies, are considered to (temporally) lack proper immunological control over endogenous latent EBV, resulting in increased viral reactivation and replication and re-expression of immunogenic early antigens, as observed in "stress" and "fatigue" cohort studies (Glaser et al 2005;Lerner et al 2012), but which are also observed in patients with certain autoimmune disorders, such as SLE and RA (Ballandraud et al 2004;Lossius et al 2012), and nasopharyngeal carcinoma (Paramita et al 2007). …”
Section: Ebv Humoral Immune Responses As Defined By Classic Serology mentioning
confidence: 99%
“…It is also relevant to highlight that EBV-reactive CD8 + T cells are enriched in or near the diseased organs of patients with rheumatoid arthritis (44,45) and MS (46), including a high proportion of T cells specific for BZLF1 (47). This could reflect a local immune response against EBV in the diseased organs, or nonspecific homing of virus-specific T cells to inflamed sites (48).…”
Section: Discussionmentioning
confidence: 99%
“…Til tross for at gjennomgått Epstein-Barrvirusinfeksjon er meget vanlig i den generelle voksne befolkningen (90 -95 %), er dette viruset sterkt assosiert med utvikling av multippel sklerose (18). Tilnaermet alle voksne pasienter med sykdommen har gjennomgått en slik virusinfeksjon, og en prospektiv studie viste at dette skjer før debut av symptomer på multippel sklerose (19).…”
Section: Epstein-barr-virusunclassified
“…To forhold tyder på at ungdomsårene er den viktigste sårbarhetsperioden for EpsteinBarr-viruseksponering: I områder hvor primaer infeksjon skjer tidlig, er forekomsten av multippel sklerose lav, og infeksiøs mononukleose, som skyldes primaer Epstein-Barrvirusinfeksjon i ungdomsårene, dobler risikoen for multippel sklerose (18).…”
Section: Epstein-barr-virusunclassified
See 1 more Smart Citation